Passive air sampler as a tool for long-term air pollution monitoring: Part 1. Performance assessment for seasonal and spatial variations - Klánová, Jana; Kohoutek, Jirí; Hamplová, Lenka; Urbanová, Petra; Holoubek, Ivan (Environmental pollution (Barking, Essex, 2006)
The potential of passive air sampling devices (polyurethane foam disks) to assess the influence of local sources on the quality of the surrounding environment was investigated. DEZA Valasske Mezirici, a coal tar and mixed tar oils processing plant, and Spolana Neratovice, a chemical factory with the history of high production of organochlorinated pesticides (OCPs), were selected as the point sources of PAHs, and OCPs, respectively. Levels of PCBs, OCPs and PAHs were determined for all sampling sites and sampling periods. The study brought useful data about the air concentrations of POPs in the investigated regions. More important, it provided information on the transport and fate of POPs in the vicinity of local sources of contamination useful for the estimation of their influence. Very good capability of passive samplers to reflect temporal and spatial fluctuation in concentrations of persistent organic pollutants in the ambient air was confirmed which makes them applicable for monitoring on the local scale.
Keywords: polycyklické aromatické uhlovodíky; polychlorované bifenyly; zeměpis; Humans; nebezpečné látky; chlorované uhlovodíky; Pesticide Residues; Polyurethanes; Hazardous Substances; Geography; Environmental Monitoring; Hydrocarbons, Chlorinated; Equipment Design; rezidua pesticidů; lidé; Polycyclic Aromatic Hydrocarbons; Air Pollutants; Chemical Industry; reprodukovatelnost výsledků; látky znečišťující vzduch; monitorování životního prostředí; roční období; Reproducibility of Results; polyurethany; Seasons; design vybavení; Czech Republic; chemický průmysl; Česká republika; Polychlorinated Biphenyls